The Role of the Transportation Sector in Serbia’s Macroeconomic Performances - Miljković, Marko; Nikolić, Ivan (Industrija, 2025)
The transportation sector plays a significant role in the functioning of the entire economy. In the literature, the channels of the influence of transport on various economic variables are theoretically explained, and there are also many empirical verifications of the positive impact on economic growth, productivity and employment above all. The aim of this paper is to analyze the importance and role of the transportation sector in the macroeconomic framework of Serbia. The contributions of the transportation sector to the gross value added and its real growth, the structure of gross value added, investments in fixed assets, employment, average net earnings and real growth of net earnings, inflation, as well as the business results of transport companies in terms of the value of total assets, operating income and net results are analyzed. Special attention is paid to the entire transportation sector, as well as to special divisions of this sector such as land transport and transport via pipelines, water transport, air transport, warehousing and support activities for transportation and postal and courier activities. The analysis covers a five-year period from 2019 to 2023.